Developing and implementing the four-dimensional aesthetic education framework in elementary education - Yang, Mei; Zhang, Jingru; Yahaya, Wan Ahmad Jaafar Wan; Yang, Yong (Frontiers in Education, 2025)
IntroductionUnder the background of sustainable development, aesthetic education is becoming increasingly important in primary education programs. This study integrates the principles of sustainable development with aesthetic education and, based on the characteristics of primary education majors, proposes the “Four-Dimensional Aesthetic Education” (4DAE) framework. This framework includes four progressive dimensions: “Process Path,” “Capacity Building,” “Individual Growth,” and “Value Orientation.” It aims to build a coordinated system that connects aesthetic perception, educational ability, personal development, and value cultivation.ObjectiveThe study explores the feasibility and effectiveness of applying the 4DAE framework in the Art course for primary education majors, and examines its impact on students’ overall competencies.MethodsThe participants were 49 first-year students majoring in primary education at a teacher training college in Jiangsu Province, China. A 12-week aesthetic education intervention was designed and implemented, focusing on the first dimension, which includes four sub-dimensions: “Perception and Experience,” “Thinking and Judgment,” “Practice and Innovation,” and “Education and Transmission.” Pre- and post-course paired questionnaires were used to assess changes in students’ overall abilities.ConclusionThe results showed that the 4DAE framework significantly improved students’ artistic perception, critical thinking, creativity, and teaching communication skills (p < 0.05). The course satisfaction rate reached 90%, showing that the course design and content met student needs. The study suggests that the 4DAE framework helps improve curriculum structure and supports the development of pre-service teachers’ core abilities. It also provides theoretical and practical guidance for implementing aesthetic education under the goal of sustainable development.